Faktor-Faktor Yang Mempengaruhi Manajemen Laba - Sylvia, Sylvia; Cecilia, Cecilia; Kyoko, Kyoko (Universitas Hamzanwadi, 2025)
Using company size as a moderating variable, this study attempts to assess the impact of profitability, liquidity, and solvency on earnings management. Companies listed on the IDX80 Indonesia Stock Exchange between 2022 to 2024 make up the study population. There were 61 firm samples and 183 observations in total. Purposive sampling was employed as the sample technique, and the SmartPLS version 3.2.9 application was tested using the Two-Stage Approach testing method. According to the study's findings, profitability positively affects earnings management, while liquidity and solvency have little bearing on it. The relationship between profitability, liquidity, and solvency with earnings management cannot be moderated by the size of the company